Rebranding Liverpool as the European Capital of Culture 2008: Cultural Value or Cultural Vandalism? - Hanlon, Alexandra (2010)
The European Capital of Culture event is one that has increasingly grown in significance as cities have recognised the potential benefits that it can bring. This dissertation assesses the socio-cultural impacts of the 2008 award on the city of Liverpool. The rebranding of Liverpool through the European Capital of Culture event is assessed through the eyes of both residents and non-residents using Anholt’s (2006) city branding framework. A further evaluation of residents’ attitudes towards the current branding is also made. Particular attention is paid to who the branding is directed at and furthermore, whether or not the unique authentic culture of the city has been preserved. Results indicate that those who do not live in Liverpool do not hold the branding in very high regard. Similarly, local residents largely feel that whilst overall the local culture has been maintained, the current branding largely prioritises tourists over residents. A concentration on incorporating local residents into the city’s representation is suggested, alongside a reworking of the current brand in order to allow non-residents to realise the city’s socio-cultural assets.